MANAJEMEN PENGELOLAAN KELAS MELALUI JOYFUL LEARNING - Widayanti, Febi Dwi (FKIP Universitas Wisnuwardhana, 2014)
Joyful learning is learning strategy that can be applied by teachers in creating fun learning while stimulating the creativity of students in learning. Based on observations, there are still many learning processes in the class that are packaged less attractive to students, so joyful learning can be an alternative in the application of classroom learning. This study aims to determine the application of joyful learning in increasing motivation and learning outcomes. Data obtained from the value of learning outcomes as well as data carried out verbally, so that this study is classified as quantitative descriptive research. In this study, some forms of joyful learning developed include teaching material concepts presented in the form of poetry and songs. At the end of the learning activities students were also asked to pour their creativity to make material concepts in the form of poetry and songs. So that by implementing fun learning, motivation and learning outcomes can be improved.